Prevalence of Microbe in Pindang Product at UKM Scale at Pelabuhan Ratu, Sukabumi District - Fia Sri Mumpuni; Sawarni Hasibuan (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2018)
Pindang, boiled fish, is one of traditional fish processing products consumed by Indonesian society. Pindang industry at Pelabuhan Ratu, District of Sukabumi, is one of central of fish boiling production in Indonesia with small and medium-sized enterprises (SMEs) scale. The previous result of gap assessment on this SMEs at Pelabuhan Ratu, District of Sukabumi showed that they have not yet applied good manufacturing practices well. Factory cleanliness and sanitation do not meet the requirements of good manufacturing practices. Thus, the research aimed to determine prevalence of microbes on baby tuna fish boiling/pindang product. The research used the proposive sampling method. Samples were taken from producer of baby tuna pindang/fish boiling at Pelabuhan Ratu, District of Sukabumi. The results of the research showed that the prevalence of microbes were TPC 100%, Yeast 100%, Escherichia coli (> 3 APM/g)10%, and Salmonella 80%.